Faktor-faktor yang berhubungan dengan keaktifan kepesertaan BPJS kesehatan di kalangan pekerja informal pada pedagang - Florencia Tamba; Dwi Noerjoedianto; Andy Amir (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Active participation by the social health insurance administration agency among informal workers remains a challenge in supporting the achievement of universal health insurance in Indonesia. Market traders, as part of the informal sector, have levels of participation and activity influenced by various factors such as knowledge, perception, income, and education. Purpose: To determine the relationship between knowledge, perception, income, and education with the active participation of traders in social health insurance administration agency. Method: This study used a quantitative design with a cross-sectional approach. The study was conducted from January to March 2026 at Angso Duo Market in Jambi City, with a sample of 98 respondents. Data were collected using a questionnaire and analyzed univariately and bivariately using the chi-square test. Results: The majority of respondents had high knowledge (79.6%), neutral perception (57.1%), high income (51.0%), and active BPJS membership status (85.7%). The bivariate analysis results showed a relationship between knowledge (p-value = 0.032), perception (p-value = 0.041), and income (p-value = 0.027) and active participation of the social health insurance administration agency. Meanwhile, education was not associated with active participation of the social health insurance administration agency (p-value = 0.218). Conclusion: Knowledge, perception, and income are associated with active participation of the social health insurance administration agency, while education level did not have a significant relationship. Suggestion: Future research can examine other variables related to active participation of the social health insurance administration agency among informal workers, especially traders. Keywords: Active Participation; Informal Workers; Knowledge; Market Traders; Social Health Insurance Administration Agency.